A Herd Outbreak Study On Contagious Ecthyma (ORF) Occurrence in Thanjavur Black Goats - Maheshwari, S.; Nithiselvi, R.; Thomas, K. Shibi (International Journal of Livestock Research, 2024)
A study on the occurrence of contagious ecthyma in Thanjavur black goats was done in Livestock Farm Complex, Veterinary College and Research Institute, Orathanadu in September 2023. Scabby proliferative dermatitis and pustular lesions on the commissures of the lips, ulcerative lesions on the tongue, gums, inner side of the lips, and lesions on the teat were observed in 36 goats out of the 42 animals maintained. Streptopenicillin 2.5g at the dose rate of 1ml/25kg body weight, anti-inflammatory drug metamizole sodium (Analgin) at the dose rate of 2 ml per animal, and antihistamine drugs chlorpheniramine maleate at the dose rate of 0.5mg /kg body weight was given intramuscularly for five days. The lesion was washed with a 1% potassium permanganate solution and a paste prepared with one part of boric acid and two parts of glycerine was topically applied on the lesions twice daily for 10 days to completely heal wounds.